The Impact of Marketing Mix on Osmo Probolinggo Mineral Water Customer Satisfaction - ngatimun ngatimun (Universitas Islam Balitar, 2022)
In order for the company to be optimal in marketing its products on the market, it needs a set of marketing equipment in the form of a marketing mix. Kthe concept of marketing mix in the form of product, price, and distribution as well as promotion; is a variable used by entrepreneurs so that consumer satisfaction is met and the needs and desires of consumers are served. (Swastha, 2005). Lingga Mas wants existing customers to be maintained, the marketing mix concept needs to be maximized. The research aims to analyzeinfluence of marketing mix (element) with satisfaction.A sample of 45 people using a population technique or saturated sampling. The research instrument was a questionnaire with a Likert scale measurement. Data were analyzed by multiple regression.There is a significant effect between Marketing Mix and Customer Satisfaction with Mineral Water Osmo Probolinggo because F count 14,068 > 2.61 (table), and sig. 0.000 < 0.05. The effect of product with satisfaction is t = 2.254 > 2.021 (t-table) and sig is 0.030 <0.05, it is concluded that there is a significant/meaningful effect, the effect of price and satisfaction is obtained tcount 4.840 > 2.021 (ttable) with sig. of 0.000 <0.05, it can be concluded that there is a significant/significant effect. Distribution with satisfaction has a significant/convincing effect because t-count is 2.121 > 2.021 with sig. 0.040 < 0.05. The promotion variable with customer satisfaction has no significant effect because tcount < ttable is 1.023 < 2.021 sig. 0.312 > 0.05. The price variable has the largest Beta Coefficients value, which is 0,